Relations Between Parental and Child Separation Anxiety: The Role of Dependency-Oriented Psychological Control. - Stone, Lisanne; Otten, Roy; Soenens, Bart; Engels, Rutger; Janssens, Jan (Journal of Child & Family Studies, 2015)
Although separation anxiety is prevalent in young children, it remains unclear whether and how maternal separation anxiety is related to separation anxiety in children. This study examined associations between maternal separation anxiety and separation anxiety in children, and the potential effect psychologically controlling parenting. Mothers (N = 269) and children (N = 287) recruited for a community sample participated in two 1-year interval data-waves. Children were aged five-eight and were interviewed using an age-appropriate method for obtaining self-reports of separation anxiety and perceptions of dependency-oriented psychologically controlling parenting. Mothers reported on their feelings of separation anxiety regarding their child via a questionnaire. We found that maternal separation anxiety was positively related to separation anxiety in children within, but not over time. We did not find psychologically controlling parenting to mediate this association. Studying other factors than parenting may be an important avenue for future research in explaining separation anxiety in children.